Mutation Analysis and Restriction Site Mapping of GDF9 in Indonesian Bligon Goat - T. Hartatik; F. A. Z. Chairunissa; S. Bintara; F. J. Fadilllah; N. P. Ningrum; D. Puspitasari; Kustantinah (Faculty of Animal Science, Bogor Agricultural University, 2023)
Bligon goat is one of the crossbred goats raised in Indonesia, which has a prolific nature, potentially increasing the economic benefits. The gene that particularly influences prolific traits is Growth Differentiation Factor 9 (GDF9). This study aims to identify the mutation analysis (SNPs and amino acid changes) and restriction enzymes map in the GDF9 of Bligon goats. Six pairs of primers were used to amplify target sequences of GDF9 by polymerase chain reaction method and continued by sequencing. The sequence products were analyzed to get information on the SNPs and restriction enzyme (RE) around the SNPs for genotyping by PCR-RFLP method. A total of 15 SNPs were found in position g.1956A>C, g.2248G>T, g.2470A>T, g.2172DelA (shift T, Heterozygote), g.2807C>T, g.2919C>T, g.2996C>T, g.3615T>C, g.3855A>C, g.3879A>G, g.3924A>G, g.3943G>T, g.3969G>A, g.3981G>A, and g.4314C>T. Eight out of fifteen SNPs are located at the exon. Thus, the amino acid shows one synonymous at Exon 1 (Leucine to Leucine) and seven non synonymous at exon 2 with varied amino acid alteration (Valine to Alanine, Glutamine to Proline, Lysine to Arginine, Lysine to Arginine, Glutamine to Histidine, Arginine to Lysine, and Serine to Asparagine, respectively). Two SNPs at position g.1956A>C in Exon 1 and g.3855A>C in exon 2 show the homozygote CC and heterozygote AC. The most sample at those two position 67% and 83% homozygote type, respectively. Recognitions of site restriction enzymes BsaI and BsmAI were found at g.1956A>C or g.667C>M (Exon I). SNP g.3855A>C or g.2566C>M was recognized by three restriction enzymes (MspI, HapII, and HpaII). Two SNPs were not recognized by the restriction enzyme, and two other SNPs have more than 12 fragmented sequences, and as a consequence, it is very difficult to analyze the genotype. In conclusion, fifteen site mutations were identified; however, only two potential genetic markers with transversion mutations in Exon 1 and Exon 2 were recognized by restriction enzymes (BsaI, HapII, and MspI). These enzymes were recommended as candidate markers for further genotype identification using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method.